2018
DOI: 10.3390/app8122573
|View full text |Cite
|
Sign up to set email alerts
|

Control of Porosity in Parts Produced by a Direct Laser Melting Process

Abstract: Recent advances in direct laser melting (DLM) have demonstrated its great potential for manufacturing three-dimensional porous metal parts. Various combinations of powder layering and processing parameters can be set to adjust the porous properties of the final parts. This study presents the effects of powder morphologies and process parameters on porosity formation during DLM. Four types of Fe-powders composed of spherical or non-spherical particles with different sizes were experimentally investigated. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Irrinki et al [14] investigated the processability of three WA powders and one GA 17-4-PH stainless steel powder and found that the GA powder generally yielded parts with less porosity, but were able to process the WA powder into parts with comparable densities and mechanical properties at sufficiently high energy densities. Jeon et al [15] processed four Fe-powders, of which three were mixtures of spherical and non-spherical powders. They found an increase in the part porosity of blended powders for increasing size misfit between the spherical and non-spherical powders.…”
Section: Introductionmentioning
confidence: 99%
“…Irrinki et al [14] investigated the processability of three WA powders and one GA 17-4-PH stainless steel powder and found that the GA powder generally yielded parts with less porosity, but were able to process the WA powder into parts with comparable densities and mechanical properties at sufficiently high energy densities. Jeon et al [15] processed four Fe-powders, of which three were mixtures of spherical and non-spherical powders. They found an increase in the part porosity of blended powders for increasing size misfit between the spherical and non-spherical powders.…”
Section: Introductionmentioning
confidence: 99%
“…Because the gas atoms are released from the lattice in the heat-affected zone, yielding a longer liquid lifetime in samples with a high weight percentage of reinforcement, e.g., 7 wt%, may result in the formation of a higher amount of gas. It is reported that this phenomenon may cause the formation of porosity in SLM-produced parts [35]. This was explored by multi-line formation tests shown in Figure 7, where the presence of cracks is evident in the reinforced sample with 7 wt% Al 2 O 3 -ZrO 2 , seen in Figure 7f.…”
Section: Temperature Distribution and Liquid Lifetimementioning
confidence: 94%
“…It often incorporates computer-controlled lasers as power sources and produces near-net shapes with sufficiently accurate dimensions as the final product [ 55 ] to eliminate the need for rough machining, making it popular in industry [ 52 , 53 , 56 , 57 ]. Due to characteristics such as its great reliability [ 53 , 54 , 58 ] and the low porosity [ 59 , 60 , 61 ] of the final products, LENS is widely employed in the customization and repair of intricate mechanical parts, including turbine blades [ 54 , 62 , 63 , 64 , 65 , 66 ]. The ability to control, independently, the powder flow from separate powder feeders in LENS allows for creating chemical gradients in the AM components [ 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Methodsmentioning
confidence: 99%